Inspiratory muscle training facilitates liberation from mechanical ventilation in subacute critically ill patients—a randomized controlled trial - Shu-Jane Wang; Tien-Pei Fang; Tien-Pei Fang; Daniel D. Rowley; Nan-Wei Liu; Jui-O Chen; Jui-Fang Liu; Jui-Fang Liu; Hui-Ling Lin; Hui-Ling Lin; Hui-Ling Lin (Frontiers in Medicine)
BackgroundPatients undergoing mechanical ventilation often develop rapid diaphragmatic atrophy, respiratory muscle weakness, and dysfunction, which are associated with prolonged duration of ventilation. This study aimed to evaluate whether Inspiratory Muscle Training (IMT) facilitates weaning from mechanical ventilation and enhances muscle strength in critically ill, subacute adult patients, while examining the relationship between IMT and relevant clinical laboratory values.MethodsIn this randomized clinical trial, patients admitted to the intensive care unit requiring mechanical ventilation for more than 2 days, with stable hemodynamics and resolved acute conditions, were enrolled. Participants were randomly assigned to the IMT or no-IMT group. The IMT group received training twice daily, 5 days a week, for three consecutive weeks. The primary outcome was ventilator duration. The primary outcome measure was the number of days until liberation from mechanical ventilation. The secondary outcomes of interest were respiratory muscle strength and biomarker levels.ResultsThirty-three subjects (17 in the IMT group, 16 in the no-IMT group) were included in the final analysis. The IMT group had significantly shorter ventilator days (12.6 ± 5.2 vs. 18.1 ± 8.8, p = 0.04). IMT intervention significantly reduced rapid shallow breathing index and improved respiratory muscle strength, with greater maximum inspiratory pressure (p < 0.01), maximum expiratory pressure (p = 0.03), and peak expiratory flow (p = 0.01). A moderate positive correlation was observed between IMT and increased creatinine levels (rs = 0.54, p = 0.01), whereas the no-IMT group showed a reduction.ConclusionIMT significantly shortened ventilator duration and improved respiratory muscle strength. A moderate correlation between increased creatinine levels and respiratory muscle strength was observed, suggesting that creatinine may be a potential biomarker for muscle recovery during IMT.Clinical trial registrationThis study was registered at ClinicalTrials.gov (NCT06611683).